Assessment of medication adherence and factors influencing nonadherence among cancer patients chemotherapy–an observational prospective study - GYANA PRASUNA SOKKI; SHEBA REJI; ELDHOSE KURIAKOSE (International Journal of Pharma and Bio Sciences, 2018)
According to World Health Organization, Cancer is the uncontrolled growth of cells, which can invade and spread to distant sites of the body. Cancer can lead to severe health consequences and conditions possibly leading to death. In cancer patients, poor adherence to medication may lead to medical complications, more frequent doctor visits and longer hospitalizations. This hospital based case study was undertaken with the objective of determining barriers of medication adherence in patients receiving chemotherapy, determining the type of cancer showing less adherence rates among the prescribed chemotherapy regimens, and to determine the regimen to which patients showed the least adherence rates. Out of the 174 patients studied, 75.8% were found to be adherent and 24.1% to be non-adherent to the prescribed chemotherapy. Majority of patients were diagnosed with breast cancer (15.51%), head and neck cancer (14.9%) and ovarian cancer (13.21%). Of the prescription sheets reviewed,20.6% were prescribed with Taxol (175mg/m2 IV) and Carbo 5 AUC (maximum dose 800mg/body) regimen and 19.5% were receiving cisplatinalone (50 mg in 1pint normal saline given IV for half hour).Among the various regimens prescribed AC (Adriamycin 60mg/m2 and Cyclophosphamide 600mg/m2) regimen (21.4%) has shown more non adherence levels. Among the total number of non-adherence cases, 50% was due to patient related factors. The other barriers for adherence among patients included economic factors (23.8%) followed by social factors(9.5%), drug related(14.2%) and the least non adherence was seen due to disease related factors(2.3%). From the present study it was concluded that patient related factors significantly affect the adherence levels. It was observed that most of the patients miss or delay their chemotherapy cycle due to lack of convenience and forgetfulness of attending the chemotherapy cycle appointments according to the date prescribed by the oncologist, and also due to lack of knowledge about the benefits and risks associated in receiving chemotherapy. This study reassures the role of adherence with treatment regimens in patient survival and better quality of life.